A Pr-doped metal oxide / La-Y-Ni composite material and its preparation method and application

The preparation of Pr doped metal oxides through supercritical CO2 fluid technology and recombined with La-Y-Ni hydrogen storage alloy, solving the problem of insufficient discharge performance and cycle stability of the hydrogen storage alloy, achieving efficient discharge capacity and long life Cyclic stability.

CN115312738BActive Publication Date: 2025-02-14YANSHAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211064940.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-01
Publication Date
2025-02-14
Estimated Expiration
2042-09-01

AI Technical Summary

Technical Problem

The discharge performance and cycle stability of existing hydrogen storage alloys are insufficient, making it difficult to meet the needs of high-energy and green nickel-hydrogen batteries.

Method used

Supercritical CO2 fluid technology is used to dopant rare earth Pr to metal oxides, prepare Pr doped metal oxides, and recombinate them with La-Y-Ni hydrogen storage alloy to produce Pr doped metal oxide/La-Y-Ni Composite material.

Benefits of technology

The maximum discharge capacity and cycle stability of the hydrogen storage alloy are improved, and especially at a temperature environment of 30°C and 40°C to 60°C, it shows a discharge performance better than the reference alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115312738B_ABST
    Figure CN115312738B_ABST
Patent Text Reader

Abstract

The present invention discloses a Pr-doped metal oxide / La-Y-Ni composite material and a preparation method and application thereof. The preparation method of the Pr-doped metal oxide / La-Y-Ni composite material adopts supercritical CO2 fluid technology to dope rare earth Pr into metal oxide to obtain Pr-doped metal oxide; then the Pr-doped metal oxide is compounded with La-Y-Ni hydrogen storage alloy to obtain Pr-doped metal oxide / La-Y-Ni composite material. Applying it in the field of batteries can improve discharge capacity and cycle stability. The preparation method of the present invention is simple, easy to operate, and low in cost, and provides a new idea for doping and composite modification of high-performance battery electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a Pr-doped metal oxide / La-Y-Ni composite material and a preparation method and application thereof. Background Art

[0002] With the increasingly serious environmental pollution and the emergence of the traditional energy crisis, many countries in the world have carried out large-scale research and development of new energy. Hydrogen, as a clean and efficient renewable energy, has attracted great attention, especially in the application of nickel-hydrogen batteries.

[0003] Nickel-metal hydride battery is a battery with hydrogen storage alloy as negative electrode material. It is a high-energy, green secondary battery and an ideal power source for hybrid electric vehicles. The technical key to the performance of MH / Ni battery is to improve the performance of negative electrode material hydrogen storage alloy. Studies have shown that adding metal oxides to hydrogen storage alloys can increase the maximum discharge capacity and cycle stability of the alloy to a certain extent, and improve the electrochemical properties of the alloy.

[0004] However, hydrogen storage materials with better discharge performance are still the research and development pursuit of those skilled in the art. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a Pr-doped metal oxide / La-Y-Ni composite material and a preparation method and application thereof.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The invention provides a method for preparing a Pr-doped metal oxide / La-Y-Ni composite material. The method comprises the following steps: using supercritical CO2 fluid technology to dope rare earth Pr into metal oxide to obtain the Pr-doped metal oxide; and then compounding the Pr-doped metal oxide with a La-Y-Ni hydrogen storage alloy to obtain the Pr-doped metal oxide / La-Y-Ni composite material.

[0008] Further, the method comprises the following steps: taking a metal oxide precursor and preparing a 1wt.% to 3wt.% Pr(NO3)3 stock solution for standby use; placing the Pr(NO3)3 stock solution and the metal oxide precursor with a concentration of 0.5mol / L to 1.5mol / L, as well as a CO2 solvent and acetic acid with a concentration of 6mol / L in an observation tank under stirring, and then adding acetic acid and carbon dioxide and controlling the pressure and temperature to form a reaction mixture; stirring the reaction mixture to form a gel and aging it for 5 to 7 days; continuously using sc The gel is washed with CO2 to form a synthetic material; the synthetic material is calcined in air and kept warm, and then cooled to room temperature to obtain a Pr-doped metal oxide; metal La, metal Y and metal Ni are placed in a smelting furnace from bottom to top in the order of melting point from low to high, and are smelted at high temperature and turned over to obtain a La-Y-Ni hydrogen storage alloy; the La-Y-Ni hydrogen storage alloy and the Pr-doped metal oxide are placed in a ball mill, and ball milling is performed under the protection of an inert gas to obtain a Pr-doped metal oxide / La-Y-Ni composite material.

[0009] Furthermore, the mass ratio of the Pr-doped metal oxide to the La-Y-Ni hydrogen storage alloy is (1:99) to (1:9).

[0010] Furthermore, the metal oxide is TiO2, ZrO2, SiO2 or Al2O3; the La-Y-Ni hydrogen storage alloy is LaY2Ni 9.5 Mn 0.5 Al 0.5 .

[0011] Furthermore, in the step of subsequently adding acetic acid and carbon dioxide and controlling the pressure and temperature, the pressure is controlled to be 3000psig to 6000psig and the temperature to be 40°C to 60°C.

[0012] Furthermore, in the step of continuously using scCO2 to wash the gel to form a synthetic material, the gel is washed with scCO2 at a flow rate of 0.5 mL / min under an environment of pressure of 3000 psig to 6000 psig and temperature of 40°C to 60°C, and the exhaust flow rate is controlled to be 0.5 mL / min.

[0013] Furthermore, in the step of cooling the synthetic material to room temperature after calcining and keeping it warm in the air, the synthetic material is calcined in the air at a temperature environment of 400°C to 600°C at a heating rate of 10°C / min, the keeping time is 2h, and the cooling rate to room temperature is 0.5°C / min.

[0014] Furthermore, the ball milling treatment lasts for 0.5 h to 2 h.

[0015] The present invention also provides a Pr-doped metal oxide / La-Y-Ni composite material, such as the Pr-doped metal oxide / La-Y-Ni composite material prepared by the above-mentioned method for preparing the Pr-doped metal oxide / La-Y-Ni composite material.

[0016] The present invention also provides the application of the above-mentioned Pr-doped metal oxide / La-Y-Ni composite material in the battery field.

[0017] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:

[0018] The present invention provides a Pr-doped metal oxide / La-Y-Ni composite material and a preparation method and application thereof. Compared with common hydrogen storage materials, the performance of the hydrogen storage composite material with added nano metal oxide is better than that of a reference alloy under certain conditions, and the application thereof in the field of batteries can improve the discharge capacity and cycle stability. Specifically: (1) The maximum discharge capacity of the Pr-doped metal oxide / La-Y-Ni composite material can reach 295 mA·h / g at a charge and discharge current density of 60 mA / g under a temperature environment of 30°C; (2) The cycle life of the Pr-doped metal oxide / La-Y-Ni composite material can reach more than 100 cycles under a temperature environment of 30°C; (3) The discharge capacity of the Pr-doped metal oxide / La-Y-Ni composite material under a high temperature environment of 40°C to 60°C is higher than that of the reference alloy. At the same time, the preparation method of the Pr-doped metal oxide / La-Y-Ni composite material is simple, easy to operate, and low in cost, and provides a new idea for the doping and composite modification of high-performance battery electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplifications do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.

[0020] Figure 1 is a graph showing the relationship between the discharge capacity and the number of cycles of the Pr-doped metal oxide / La-Y-Ni composite material used as an electrode obtained in Example 1 of the present invention;

[0021] Figure 2 is a graph showing the relationship between discharge capacity and temperature of a Pr-doped metal oxide / La-Y-Ni composite material used as an electrode obtained in Example 1 of the present invention;

[0022] Figure 3 is a diagram of an experimental device for preparing Pr-doped TiO2 metal oxide in the present invention;

[0023] Figure 3 In the figure, A-CO2 cylinder, B-syringe pump, C-observation tank, D-temperature controller, E-pressure display. DETAILED DESCRIPTION

[0024] As can be seen from the background technology, there is currently a problem of how to further improve the discharge performance of hydrogen storage alloys.

[0025] The inventors have discovered that doping modification is an important method to improve the catalytic activity of metal oxide nanomaterials. Rare earth elements have a unique 4f electron layer, and rare earth doping will cause lattice distortion of metal oxides, which significantly improves the catalytic activity of metal oxides, thereby improving the electrochemical properties of hydrogen storage alloy electrodes. In addition, the emergence of nanotechnology has injected new vitality into the development of materials. When materials enter the nanoscale, they show excellent performance in catalysis, light, electricity and thermodynamics. Supercritical fluid technology is an emerging technology for preparing ultrafine nanopowders. Powder materials prepared by traditional methods have low specific surface area and severe agglomeration.

[0026] Supercritical fluid refers to a fluid whose temperature and pressure are above the critical temperature and critical pressure. It has the properties of both gas and liquid, with strong diffusivity and good solubility. The use of supercritical technology to assist the synthesis of nano-metal oxide materials is a new technology developed in recent years. Supercritical carbon dioxide is the most widely used supercritical fluid. The critical temperature of supercritical carbon dioxide is T C =31.1℃, critical pressure is P C =7.38MPa, non-toxic, non-polluting, low-priced, widely available, supercritical conditions can be easily achieved. Supercritical carbon dioxide fluid technology provides an excellent reaction medium for the preparation of metal oxide nanoparticles. Controlling its technical parameters (such as density, temperature, pressure and dielectric properties, etc.) can better control the supersaturation process, thereby better controlling the product morphology. Preventing the agglomeration and coagulation of primary nanoparticles is of great significance for the preparation of nanomaterials.

[0027] The present invention adopts supercritical CO2 fluid technology to prepare Pr-doped TiO2 metal oxide, and the prepared Pr-doped TiO2 metal oxide is co-milled with hydrogen storage material to prepare Pr-doped metal oxide / La-Y-Ni composite material, so as to improve its discharge capacity and cycle stability as a hydrogen storage alloy electrode.

[0028] The invention provides a method for preparing a Pr-doped metal oxide / La-Y-Ni composite material. The method comprises the following steps: using supercritical CO2 fluid technology to dope rare earth Pr into metal oxide to obtain the Pr-doped metal oxide; and then compounding the Pr-doped metal oxide with a La-Y-Ni hydrogen storage alloy to obtain the Pr-doped metal oxide / La-Y-Ni composite material.

[0029] Further, the method comprises the following steps: taking a metal oxide precursor and preparing a 1wt.% to 3wt.% Pr(NO3)3 stock solution for standby use; placing the Pr(NO3)3 stock solution and the metal oxide precursor with a concentration of 0.5mol / L to 1.5mol / L, as well as a CO2 solvent and acetic acid with a concentration of 6mol / L in an observation tank under stirring, and then adding acetic acid and carbon dioxide and controlling the pressure and temperature to form a reaction mixture; stirring the reaction mixture to form a gel and aging it for 5 to 7 days; continuously using sc The gel is washed with CO2 to form a synthetic material; the synthetic material is calcined in air and kept warm, and then cooled to room temperature to obtain a Pr-doped metal oxide; metal La, metal Y and metal Ni are placed in a smelting furnace from bottom to top in the order of melting point from low to high, and are smelted at high temperature and turned over to obtain a La-Y-Ni hydrogen storage alloy; the La-Y-Ni hydrogen storage alloy and the Pr-doped metal oxide are placed in a ball mill, and ball milling is performed under the protection of an inert gas to obtain a Pr-doped metal oxide / La-Y-Ni composite material.

[0030] Furthermore, the mass ratio of the Pr-doped metal oxide to the La-Y-Ni hydrogen storage alloy is (1:99) to (1:9).

[0031] Furthermore, the metal oxide is TiO2, ZrO2, SiO2, Al2O3, etc.; the La-Y-Ni hydrogen storage alloy is LaY2Ni 9.5 Mn 0.5 Al 0.5 .

[0032] Furthermore, in the step of subsequently adding acetic acid and carbon dioxide and controlling the pressure and temperature, the pressure is controlled to be 3000psig to 6000psig and the temperature to be 40°C to 60°C.

[0033] Furthermore, in the step of continuously using scCO2 to wash the gel to form a synthetic material, the gel is washed with scCO2 at a flow rate of 0.5 mL / min under an environment of pressure of 3000 psig to 6000 psig and temperature of 40°C to 60°C, and the exhaust flow rate is controlled to be 0.5 mL / min.

[0034] Furthermore, in the step of cooling the synthetic material to room temperature after calcining and keeping it warm in the air, the synthetic material is calcined in the air at a temperature environment of 400°C to 600°C at a heating rate of 10°C / min, the keeping time is 2h, and the cooling rate to room temperature is 0.5°C / min.

[0035] Furthermore, the ball milling treatment lasts for 0.5 h to 2 h.

[0036] The present invention also provides a Pr-doped metal oxide / La-Y-Ni composite material, such as the Pr-doped metal oxide / La-Y-Ni composite material prepared by the above-mentioned method for preparing the Pr-doped metal oxide / La-Y-Ni composite material.

[0037] The present invention also provides the application of the above-mentioned Pr-doped metal oxide / La-Y-Ni composite material in the battery field.

[0038] The technical solution of the present invention is as follows:

[0039] (1) Preparation of Pr-doped metal oxides

[0040] Pr-doped metal oxides were prepared using supercritical CO2 fluid technology.

[0041] (2) Preparation of La-Y-Ni hydrogen storage alloy

[0042] The hydrogen storage alloy samples are made of metals with a purity of more than 99.9% in a stoichiometric ratio and are melted by vacuum arc in an argon atmosphere. Different melting currents and times are used according to the melting points and vapor pressures of different metals. In order to ensure that the alloy composition and structure are as uniform as possible, the alloy block samples are turned over and melted two to three times. The obtained alloy is mechanically crushed and ground to 200 mesh for electrode preparation and performance testing.

[0043] (3) Preparation of Pr-doped metal oxide / La-Y-Ni composites

[0044] A certain ratio of Pr-doped metal oxide powder and La-Y-Ni hydrogen storage alloy are placed in a ball mill, high-purity argon is used as a protective gas, and ball milled for a certain period of time, so that a hydrogen storage composite material can be prepared.

[0045] (4) Hydrogen storage alloy performance test

[0046] The alloy powder was pressed into sheets and made into simulated batteries to test its electrochemical performance. The electrochemical performance was tested using a battery tester. The maximum discharge capacity was tested at a current density of 60 mA / g.

[0047] The present invention is described in detail below in conjunction with specific implementation modes.

[0048] Example 1

[0049] (1) Preparation of Pr-doped metal oxides

[0050] Example 1 uses Figure 3 The experimental setup shown. Pr-doped metal oxides were synthesized in a 10 mL stainless steel reactor connected to a syringe pump and supercritical CO2. The syringe pump was used to pump CO2 into the reactor. The temperature and pressure in the reactor were measured and controlled using thermocouples.

[0051] Titanium (IV) isopropoxide (TIP) with a purity of 97% was used as a precursor of TiO2. 1g of Pr(NO3)3·6H2O solid was dissolved in 99g of isopropanol to prepare a 1wt.% Pr(NO3)3 solution for later use.

[0052] Take 3mL (1.2mol / L) titanium (IV) isopropoxide (TIP), 1mL of 1wt.% Pr(NO3)3 stock solution, 3mL (6mol / L) acetic acid and 3mL CO2 solvent and quickly place them in a 10mL observation tank under stirring, and then heat and pressurize them to 60°C and 5000psig (approximately equal to 34MPa) with supercritical carbon dioxide (scCO2).

[0053] The reaction mixture was stirred for about 30 minutes to several hours to form a gel. After aging for 5 days, the formed gel was continuously washed with scCO2 at a controlled flow rate of 0.5 mL / min, followed by controlled exhaust at 0.5 mL / min. The synthesized material was calcined in air at 500°C with a heating rate of 10°C / min; the holding time was 2 hours, and the cooling rate to room temperature was 0.5°C / min.

[0054] (2) Preparation of La-Y-Ni hydrogen storage alloy

[0055] Take metals such as La, Y, and Ni, and place them in a smelting furnace from bottom to top in order of melting point from low to high. Smelt at high temperature and turn over two or three times to prepare La-Y-Ni hydrogen storage alloy.

[0056] The smelted La-Y-Ni hydrogen storage alloy is mechanically crushed and ground with an agate mortar to obtain La-Y-Ni hydrogen storage alloy powder.

[0057] (3) Preparation of Pr-doped metal oxide / La-Y-Ni composites

[0058] According to the mass ratio of Pr-doped metal oxide to La-Y-Ni hydrogen storage alloy powder of 3:97, Pr-doped metal oxide and La-Y-Ni hydrogen storage alloy powder were placed in a ball mill, filled with argon protection, and ball milled for 1 hour to obtain a Pr-doped metal oxide / La-Y-Ni composite material.

[0059] (4) Performance test of Pr-doped metal oxide / La-Y-Ni composite material as hydrogen storage alloy electrode

[0060] The electrochemical performance of the composite hydrogen storage material was tested using a battery tester. The Pr-doped metal oxide / La-Y-Ni composite material was mixed with the conductive powder (carbonyl nickel powder) at a weight ratio of 1:5 and cold pressed. The molding pressure was 3000Kg / cm 2 ~5600Kg / cm 2 The test electrode is in the shape of a disc, with a diameter of 1 cm and a thickness of 0.1 cm to 0.15 cm. The electrode sheet and the conductive nickel wire are welded together by a spot welder to form the negative electrode of the battery. The positive electrode uses a sintered nickel hydroxide (chemical formula is Ni(OH)2 / NiOOH) electrode sheet. The electrolyte is a 6 mol / L KOH aqueous solution.

[0061] Figure 1 1 is a graph showing the relationship between the discharge capacity and the number of cycles of the Pr-doped metal oxide / La-Y-Ni composite material as an electrode obtained in Example 1 of the present invention. It can be seen that the discharge capacity of the Pr-doped metal oxide / La-Y-Ni composite material compounded with the Pr-doped metal oxide is improved compared with the La-Y-Ni hydrogen storage alloy.

[0062] Figure 2 1 is a graph showing the relationship between the discharge capacity and temperature of the Pr-doped metal oxide / La-Y-Ni composite material as an electrode obtained in Example 1 of the present invention. It can be seen that compared with the La-Y-Ni hydrogen storage alloy, the high-temperature discharge capacity of the Pr-doped metal oxide / La-Y-Ni composite material compounded with the Pr-doped metal oxide is also higher than the benchmark.

[0063] Example 2

[0064] (1) Preparation of Pr-doped metal oxides

[0065] Example 2 uses Figure 3 The experimental setup shown. Pr-doped metal oxides were synthesized in a 10 mL stainless steel reactor connected to a syringe pump and supercritical CO2. The syringe pump was used to pump CO2 into the reactor. The temperature and pressure in the reactor were measured and controlled using thermocouples.

[0066] Titanium (IV) isopropoxide (TIP) with a purity of 97% was used as a precursor of TiO2. 1g of Pr(NO3)3·6H2O solid was dissolved in 99g of isopropanol to prepare a 1wt.% Pr(NO3)3 solution for later use.

[0067] Take 3mL (1mol / L) titanium (IV) isopropoxide (TIP), 1mL of 1wt.% Pr(NO3)3 stock solution, 3mL (6mol / L) acetic acid and 3mL CO2 solvent and quickly place them in a 10mL observation tank under stirring, then add acetic acid and carbon dioxide to the required pressure and temperature to 50°C and 3000psig (approximately equal to 20MPa).

[0068] After stirring the reaction mixture for about 30 minutes to several hours, a gel is formed. After aging for 5 days, the formed gel is continuously washed with scCO2 (6000 psig, 40°C) at a controlled flow rate of 0.5 mL / min, followed by controlled exhaust at 0.5 mL / min. The synthesized material is calcined in air at 400°C with a heating rate of 10°C / min; the holding time is 2 hours, and the cooling rate to room temperature is 0.5°C / min.

[0069] (2) Preparation of La-Y-Ni hydrogen storage alloy

[0070] Take metals such as La, Y, and Ni, and place them in a smelting furnace from bottom to top in order of melting point from low to high. Smelt at high temperature and turn over two or three times to prepare La-Y-Ni hydrogen storage alloy.

[0071] The smelted La-Y-Ni hydrogen storage alloy is mechanically crushed and ground with an agate mortar to obtain La-Y-Ni hydrogen storage alloy powder.

[0072] (3) Preparation of Pr-doped metal oxide / La-Y-Ni composites

[0073] According to the mass ratio of Pr-doped metal oxide to La-Y-Ni hydrogen storage alloy powder of 5:95, Pr-doped metal oxide and La-Y-Ni hydrogen storage alloy powder were placed in a ball mill for 1.5 hours and filled with argon gas for protection, so as to obtain a Pr-doped metal oxide / La-Y-Ni composite material.

[0074] (4) Performance test of Pr-doped metal oxide / La-Y-Ni composite material as hydrogen storage alloy electrode

[0075] The electrochemical performance of the composite hydrogen storage material was tested using a battery tester. The Pr-doped metal oxide / La-Y-Ni composite material was mixed with the conductive powder (carbonyl nickel powder) at a weight ratio of 1:5 and cold pressed. The molding pressure was 3000Kg / cm 2 ~5600Kg / cm 2The test electrode is in the shape of a disc, with a diameter of 1 cm and a thickness of 0.1 cm to 0.15 cm. The electrode sheet and the conductive nickel wire are welded together by a spot welder to form the negative electrode of the battery. The positive electrode uses a sintered nickel hydroxide (chemical formula is Ni(OH)2 / NiOOH) electrode sheet. The electrolyte is a 6 mol / L KOH aqueous solution.

[0076] Example 3

[0077] (1) Preparation of Pr-doped metal oxides

[0078] Example 3 uses Figure 3 The experimental setup shown. Pr-doped metal oxides were synthesized in a 10 mL stainless steel reactor connected to a syringe pump and supercritical CO2. The syringe pump was used to pump CO2 into the reactor. The temperature and pressure in the reactor were measured and controlled using thermocouples.

[0079] Titanium (IV) isopropoxide (TIP) with a purity of 97% was used as a precursor of TiO2. 1g of Pr(NO3)3·6H2O solid was dissolved in 99g of isopropanol to prepare a 1wt.% Pr(NO3)3 solution for later use.

[0080] Take 3mL (1.5mol / L) titanium (IV) isopropoxide (TIP), 1ml of 1wt.% Pr(NO3)3 stock solution, 3mL (6mol / L) acetic acid and 3mL CO2 solvent and quickly place them in a 10mL observation tank under stirring, then add acetic acid and carbon dioxide to the required pressure and temperature to 40°C and 6000psig (about 40MPa).

[0081] After stirring the reaction mixture for about 30 minutes to several hours, a gel is formed. After aging for 5 days, the formed gel is continuously washed with scCO2 (6000 psig, 40°C) at a controlled flow rate of 0.5 mL / min, followed by controlled exhaust at 0.5 mL / min. The synthesized material is calcined in air at 600°C with a heating rate of 10°C / min; the holding time is 2 hours, and the cooling rate to room temperature is 0.5°C / min.

[0082] (2) Preparation of La-Y-Ni hydrogen storage alloy

[0083] Take metals such as La, Y, and Ni, and place them in a smelting furnace from bottom to top in order of melting point from low to high. Smelt at high temperature and turn over two or three times to prepare La-Y-Ni hydrogen storage alloy.

[0084] The smelted La-Y-Ni hydrogen storage alloy is mechanically crushed and ground with an agate mortar to obtain La-Y-Ni hydrogen storage alloy powder.

[0085] (3) Preparation of Pr-doped metal oxide / La-Y-Ni composites

[0086] According to the mass ratio of Pr-doped metal oxide to La-Y-Ni hydrogen storage alloy powder of 1:99, the Pr-doped metal oxide and La-Y-Ni hydrogen storage alloy powder were placed in a ball mill for 0.5 h, and argon gas was filled in for protection to obtain a Pr-doped metal oxide / La-Y-Ni composite material.

[0087] (4) Performance test of Pr-doped metal oxide / La-Y-Ni composite material as hydrogen storage alloy electrode

[0088] The electrochemical performance of the composite hydrogen storage material was tested using a battery tester. The Pr-doped metal oxide / La-Y-Ni composite material was mixed with the conductive powder (carbonyl nickel powder) at a weight ratio of 1:5 and cold pressed. The molding pressure was 3000Kg / cm 2 ~5600Kg / cm 2 The test electrode is in the shape of a disc, with a diameter of 1 cm and a thickness of 0.1 cm to 0.15 cm. The electrode sheet and the conductive nickel wire are welded together by a spot welder to form the negative electrode of the battery. The positive electrode uses a sintered nickel hydroxide (Ni(OH)2 / NiOOH) electrode sheet. The electrolyte is a 6 mol / L KOH aqueous solution.

[0089] The invention relates to an electrode material prepared by using supercritical CO2 fluid technology to prepare Pr-doped TiO2 nano powder and composite it with a hydrogen storage alloy. The preparation method is simple and the composite material exhibits excellent discharge performance.

[0090] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.

Claims

1. A method for preparing a Pr-doped metal oxide / La-Y-Ni composite material, characterized in that: The rare earth Pr is doped into the metal oxide by using supercritical CO2 fluid technology to obtain the Pr-doped metal oxide; the Pr-doped metal oxide is then compounded with La-Y-Ni hydrogen storage alloy to obtain the Pr-doped metal oxide / La-Y-Ni composite material; The Pr-doped metal oxide / La-Y-Ni composite material is used as a battery electrode material; The Pr-doped metal oxide / La-Y-Ni composite material has a maximum discharge capacity of 295 mA·h / g at a charge and discharge current density of 60 mA / g under a temperature environment of 30° C., and a cycle life of greater than or equal to 100 cycles; The preparation method is characterized by comprising the following steps: Take a metal oxide precursor and prepare a 1wt.% to 3wt.% Pr(NO3)3 stock solution for use; place the Pr(NO3)3 stock solution and the metal oxide precursor with a concentration of 0.5mol / L to 1.5mol / L, as well as a CO2 solvent and acetic acid with a concentration of 6mol / L in an observation tank under stirring, then add acetic acid and carbon dioxide and control the pressure and temperature to form a reaction mixture; stir the reaction mixture to form a gel, and age it for 5 to 7 days; continuously use scCO2 to wash the gel to form a synthetic material; then calcine the synthetic material in air and keep it warm, and then cool it to room temperature to obtain a Pr-doped metal oxide; Take metal La, metal Y and metal Ni, place them in a smelting furnace from bottom to top in the order of melting point from low to high, melt them at high temperature and turn them over to obtain La-Y-Ni hydrogen storage alloy; The La-Y-Ni hydrogen storage alloy and the Pr-doped metal oxide are placed in a ball milling jar and subjected to ball milling treatment under the protection of an inert gas to obtain a Pr-doped metal oxide / La-Y-Ni composite material.

2. The method for preparing the Pr-doped metal oxide / La-Y-Ni composite material according to claim 1, characterized in that: The mass ratio of the Pr-doped metal oxide to the La-Y-Ni hydrogen storage alloy is (1:99) to (1:9).

3. The method for preparing the Pr-doped metal oxide / La-Y-Ni composite material according to claim 1, characterized in that: The metal oxide is TiO2, ZrO2, SiO2 or Al2O3; the La-Y-Ni hydrogen storage alloy is LaY2Ni 9.5 Mn 0.5 Al 0.5 .

4. The method for preparing the Pr-doped metal oxide / La-Y-Ni composite material according to claim 1, characterized in that: The step of subsequently adding acetic acid and carbon dioxide and controlling the pressure and temperature comprises controlling the pressure to be 3000 psig to 6000 psig and the temperature to be 40° C. to 60° C.

5. The method for preparing the Pr-doped metal oxide / La-Y-Ni composite material according to claim 1, characterized in that: In the step of continuously using scCO2 to wash the gel to form a synthetic material, the gel is washed with scCO2 at a flow rate of 0.5 mL / min under an environment of pressure of 3000 psig to 6000 psig and temperature of 40°C to 60°C, and the exhaust flow rate is controlled to be 0.5 mL / min.

6. The method for preparing the Pr-doped metal oxide / La-Y-Ni composite material according to claim 1, characterized in that: In the step of cooling the synthetic material to room temperature after calcining it in air and keeping it warm, the synthetic material is calcined in air at a temperature of 400°C to 600°C at a heating rate of 10°C / min, the keeping time is 2 hours, and the cooling rate to room temperature is 0.5°C / min.

7. The method for preparing the Pr-doped metal oxide / La-Y-Ni composite material according to claim 1, characterized in that: The ball milling treatment lasts for 0.5 h to 2 h.

8. A Pr-doped metal oxide / La-Y-Ni composite material, characterized in that: A Pr-doped metal oxide / La-Y-Ni composite material obtained by the method for preparing a Pr-doped metal oxide / La-Y-Ni composite material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation of La-Mg-Ni system hydrogen occluding alloy

    CN101353733A

  • Direct hydrogen storage alloy anode catalyst for borohydride fuel battery

    CN101465430A

  • Rare-earth element-doped titanium-based mesoporous titanium dioxide catalyst material and preparation method and application thereof

    CN107910561A

  • Preparation method of hydrogen storage alloy composite material

    CN110492086A